2011
DOI: 10.1007/s00439-011-1085-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes

Abstract: Postaxial Polydactyly (PAP) is characterized by fifth digit duplication in hands and/or feet. Two types of PAP including PAP-A, representing the development of well-formed extra digit, and PAP-B, representing the presence of rudimentary fifth digit, have been described. Both isolated and syndromic forms of PAP have been reported. Isolated forms of PAP usually segregate as an autosomal dominant trait and to date four loci have been identified. In the present study, we have described mapping of the first locus o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
0
35
1
Order By: Relevance
“…Affected individuals of the family, presented here, showed well-formed six digits in both hands and feet. This form of autosomal recessive PAP is clearly distinct from the one we described previously,13 as it clearly maps in a different chromosomal location. Also, the present study showed a novel phenotype of wide and deviated fifth finger on at least one hand.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Affected individuals of the family, presented here, showed well-formed six digits in both hands and feet. This form of autosomal recessive PAP is clearly distinct from the one we described previously,13 as it clearly maps in a different chromosomal location. Also, the present study showed a novel phenotype of wide and deviated fifth finger on at least one hand.…”
Section: Discussioncontrasting
confidence: 50%
“…Affected individuals in both of these families had well developed sixth digits. In the family reported by Umm-e-Kalsoom et al 13 an additional feature of hallux valgus deformity was observed in one of the affected individual. Affected individuals of the family, presented here, showed well-formed six digits in both hands and feet.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations